Development Of Sindro Application In Tahsin Al-Quran Lecture - Awal Kurnia Putra Nasution; Muhammad Hasyimsyah Batubara (Institute of Computer Science (IOCS), 2022)
The Al-Quran tahsin course requires learning media to help students learn the science of tahsin. The need for learning media in the tahsin course can be answered by developing the android tahsin application (SINDRO). This study aimed to develop an android application in the Al-Quran tahsin course and determine the quality of the application's feasibility. The research method used is the research and development/R&D research method, the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Based on these stages, it produces an android-based SINDRO application learning media (tahsin Android). The SINDRO application (Android tahsin) developed has gone through the validation stage by several experts and tahsin lecturers and is revised according to the assessment of experts and tahsin lecturers. Generally, the validation results from several experts and tahsin lecturers on the SINDRO application (android tahsin) are at a very decent qualification level. From media experts, the feasibility percentage for the SINDRO application (android tahsin) is 87.82%, for material experts are 83.63%, tahsin lecturers are 87.14%, and for small group trials the percentage of feasibility is 83.75%. So overall, the SINDRO application (android tahsin) developed has the predicate that it is very suitable to be used as a medium for learning tahsin. The application passes the software quality test based on usability quality aspects. The usability aspect resulted in an overall average of 6.02, so it passed the test in the